Evaluation of Shanghai’s Logistics Level from the Perspective of High-quality Development - Hu, Yi (International Journal of Social Sciences and Public Administration, 2024)
The thesis evaluates the logistics level of Shanghai by constructing the evaluation indexes of Shanghai logistics level under the perspective of high-quality development, setting up five first-level indexes and corresponding nine second-level indexes, adopting the data of Shanghai Municipal Bureau of Statistics from 2005 to 2022, and evaluating the logistics level of Shanghai by utilizing the factor analysis method to find out the factors that have the most influence on the high-quality development of the logistics level of Shanghai, i.e., the factor of logistics infrastructure and the factor of logistics innovation ability. factor, focusing on these two factors to make countermeasures and suggestions for Shanghai’s logistics industry, pointing out the shortcomings of the thesis and the future outlook.